The Gendered Landscape of Justice: Institutional Barriers to Women’s Khula Rights in District Courts Peshawar, Khyber Pakhtunkhwa (Journal of Social Sciences Review, 2025)
Women seeking Khula (Islamic divorce) in Peshawar courts face systemic barriers deeply embedded within patriarchal structures and gender norms. This study critically examines the intersection of legal, social, and cultural constraints that shape women's experiences in family courts. Using a qualitative approach, the research highlights the pervasive influence of patriarchal ideologies, which manifest through familial pressure, societal stigmatization, and religious interpretations that discourage women from pursuing their legal rights. The findings reveal that the legal system itself, rather than being a neutral arbiter of justice, operates within a patriarchal framework that systematically disadvantages women. Structural barriers, including judicial biases, procedural delays, and socio-cultural intimidation, further impede women’s access to justice, often compelling them to forgo legal recourse altogether. The study draws upon feminist theories of structural oppression to analyze the ways in which institutionalized patriarchy reinforces gendered disparities in legal proceedings. It argues for urgent policy interventions and legal reforms to dismantle these entrenched barriers and ensure a more equitable legal environment for women seeking Khula.
Keywords: Patriarchy; Legal System; Women’s Rights; Gendered Justice; Khula (Islamic Divorce)